2008
DOI: 10.1021/bi801683k
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of an Oncogenic Mutation That Alters Membrane Targeting: Glu17Lys Modifies the PIP Lipid Specificity of the AKT1 PH Domain

Abstract: The protein kinase AKT1 regulates multiple signaling pathways essential for cell function. Its Nterminal PH domain (AKT1 PH) binds the rare signaling phospholipid phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P 3 ], resulting in plasma membrane targeting and phosphoactivation of AKT1 by a membrane-bound kinase. Recently, it was discovered that the Glu17Lys mutation in the AKT1 PH domain is associated with multiple human cancers. This mutation constitutively targets the AKT1 PH domain to the plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(191 citation statements)
references
References 40 publications
(93 reference statements)
10
180
0
Order By: Relevance
“…Consistent with this finding, both L52R and D323H weaken PH-KD binding in two-hybrid assays. Previously, the mechanism of activation of E17K has been attributed to an altered lipid-binding specificity (10,11). Our results indicate perturbation of interdomain interactions to be an additional mechanism underlying E17K activation.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Consistent with this finding, both L52R and D323H weaken PH-KD binding in two-hybrid assays. Previously, the mechanism of activation of E17K has been attributed to an altered lipid-binding specificity (10,11). Our results indicate perturbation of interdomain interactions to be an additional mechanism underlying E17K activation.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, a somatic mutation in the PH domain of AKT1 was identified in a subset of human carcinomas (10). This mutation results in the substitution of glutamic acid at codon 17 of AKT1 with lysine (E17K) and alters the lipid-binding specificity of AKT, leading to pathological membrane association and constitutive signaling (10,11). Other than human cancers, germ-line and somatic E17K mutations in AKT have been identified in Proteus syndrome, human hypoglycemia, and hemimegalencephaly (12)(13)(14).…”
mentioning
confidence: 99%
“…It has been shown that the E17K mutation results in enhanced translocation of AKT1 to the membrane in which phosphorylation by PDK1 occurs (Carpten et al, 2007). Recent results indicate that the effect of E17K is to broaden the lipid-binding specificity of AKT such that it can bind physiological concentrations PIP2 found in the plasma membrane (Landgraf et al, 2008). It has also been shown that in the inactive state, AKT is bound to PDK1, but activation is suppressed through interaction of the PH domain with the kinase domain, preventing PDK1 access to Thr308 and preventing phosphorylation (Calleja et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…MK-2206 binds to the region that interacts with both the plekstrin homology and kinase domains, and prevents translocation of AKT to the membrane and activation. AKT1 E17K mutation alters the electrostatic interactions of the lipid binding pocket and dramatically increases the affinity of the protein for the constitutive membrane lipid PI (4,5)P2 (24), which probably explains increased membrane localization compared with wild-type AKT1. The allosteric inhibitor VIII has previously been reported to be less effective than several different catalytic inhibitors at inhibiting purified AKT1 E17K protein and proliferation of AKT1 E17K transfected fibroblasts (15), but presumably because membrane translocation is still a necessary step and/or because it is structurally distinct from inhibitor VIII, MK-2206 is still able to inhibit colony formation in vitro and inhibit tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 99%